Prospects of stem cell therapy in osteoarthritis. (May 2011) - Roberts, Sally; Genever, Paul; McCaskie, Andrew; Bari, Cosimo De
Osteoarthritis is a common disorder in which there is not only extensive degeneration but also an aberrant attempt at repair in joints. Stem cell therapy could provide a permanent, biological solution, with all sources of stem cells (embryonic, fetal and adult) showing some degree of potential. Mesenchymal stromal/stem cells, however, appear to be the leading candidates because of their ability to be sourced from many or all joint tissues. They may also modulate the immune response of individuals, in a manner influenced by local factors. This biological behavior of stem cells renders the application of regulatory standardizations challenging in comparison to pharmaceutical therapies. However, this would not be an issue if endogenous stem cells were activated to effect repair of an arthritic joint.